(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
Rolando Cárdenas was one of those men of fragile stature, occupied with silence; silence born from the strength of those who resist. He understood and respected the observer’s chair, imploring the richness of the everyday image as support for the work of the simple man not to disappear before him. Rolando Cárdenas sang about the professions, dignifying women and men and their existence in the everyday world: his poetry is one of those professions, which presupposes and provides the aesthetic image where the back is hardened, curved like a scythe to decapitate the accumulated sadness.